2009
DOI: 10.1007/s10157-009-0169-3
|View full text |Cite
|
Sign up to set email alerts
|

Pathological influence of obesity on renal structural changes in chronic kidney disease

Abstract: Background: Role of obesity on renal pathological and structural changes is not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 23 publications
2
29
1
1
Order By: Relevance
“…Renal biopsy samples showing any clinical and histologic evidence of other primary or secondary renal diseases, including diabetic nephropathy, were carefully eliminated. The appearance of an increased glomerular basement membrane thickness alone was not a criterion for exclusion because studies have suggested that obese patients or those with ORG can have an increased glomerular basement membrane thickness in the absence of diabetes (18,19). Hypertension was not an exclusion criterion.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Renal biopsy samples showing any clinical and histologic evidence of other primary or secondary renal diseases, including diabetic nephropathy, were carefully eliminated. The appearance of an increased glomerular basement membrane thickness alone was not a criterion for exclusion because studies have suggested that obese patients or those with ORG can have an increased glomerular basement membrane thickness in the absence of diabetes (18,19). Hypertension was not an exclusion criterion.…”
Section: Patient Selectionmentioning
confidence: 99%
“…A case control study comparing renal biopsies in 95 morbidly obese patients undergoing bariatric surgery with 40 control subjects identified an independent relationship between BMI and likelihood of glomerular lesions (podocyte hypertrophy, increased mesangial cellularity or increased extracellular matrix) (89). Other investigators have found obesity to be associated with glomerular hypertrophy, basement membrane thickening, and overt proteinuria (90,91).…”
Section: Conventional Ckd Risk Factors and Osamentioning
confidence: 99%
“…Esto ha sido documentado en el caso de la nefropatía por IgA en donde un IMC > 25 kg/m 2 es un buen predictor de aumento de la creatininemia 47 . En otras enfermedades como la nefroesclerosis benigna y la enfermedad de membrana basal delgada, la obesidad incrementa la proteinuria y se asocia a glomerulomegalia y engrosamiento de la membrana basal glomerular, hallazgos similares a los encontrados en la nefropatía relacionada a obesidad 48 .…”
Section: Manifestaciones Y Efecto Clínico De La Obesidad En La Evolucunclassified